Tuberculous pericarditis in adolescents: A case series - Paramitha, Winda; Murni, Indah Kartika; Arguni, Eggi; Setyowireni, Dwikisworo (Indonesian Pediatric Society, 2020)
Tuberculosis (TB) is one of the major causes of childhood mortality, especially in endemic areas. In 2013, the World Health Organization (WHO) estimated 550,000 new cases and 80,000 deaths due to TB among children. Around 70-80% of the cases were pulmonary TB, while the rest were extra-pulmonary TB.1 Tuberculous pericarditis accounts for only 8% of all TB cases, however, tuberculosis is the main cause of pericarditis in high-TB-burden countries, including Indonesia.2 The mortality rate reached 17-40% and is affected by treatment adequacy.3 Without adequate therapy, the mean life expectancy is 3.7 months, with only 20% surviving to the sixth month.4 A 2004 study reported that successful treatment of TB in children depends on several factors, such as treatment compliance, timing and accuracy of diagnosis, concurrent human immunodeficency virus (HIV) infection and its clinical stage of disease, malnutrition, and drug resistance.5 Adolescents and young adults are at the highest risks of having TB.6 We report here on three cases of tuberculous pericarditis in adolescents and their outcomes following pericardiocentesis and medication.